Effect of Oxide Scale on Hot Dip Zn-Al-Mg Alloy Coating Prepared by Reduction Combined with Induction Heating - Yijie Zhang (Metals, 2020)
Hot dipping Zn-Al-Mg coatings were prepared by rapid induction heating combined with gas protection. The influence of oxide scale on the structure and surface quality of a hot-dip Zn-6Al-3Mg alloy coating was studied in this paper. The results showed that the reaction of Fe-Al was suppressed by the scale on the surface of the steel plate. When the thickness of scale was 10 μm and the steel entry temperature was 900 °C, the surface quality of the coating was good. The Zn-Al-Mg coatings mainly consisted of the ternary eutectic structure of Zn/Al/MgZn2 and Fe4Al13 at the interface. When the scale thickness was 2–3 μm with the same steel entry temperature, the surface quality of the coating was poor, and serious stripe-like protrusion defects were formed on the surface of the coating, which was mainly caused by the Fe4Al13 phase separating from the substrate / coating interface into the overlay.